The broken life in Dostoevsky’s "Notes from the Underground" - Pieniążek, Paweł (Hybris, 2019)
This article is dedicated to a philosophical interpretation of Dostoevsky’s Notes from the Underground. In contrast to the existential interpretation proposed by Shestov (in Philosophy of tragedy) the author defends the thesis that Dostoevsky’s novel has to be interpreted from the perspective of modernity, and the tragedy of his hero, the underground man, has to be interpreted in categories of alienation and inauthentic existence. From that perspective the divide between normal life and underground life expresses the fundamental contradiction of the modern world. The author indicates the proximity between Dostoevsky’s and Kierkegaard’s and Nietzsche’s analyses of modernity. He then shows that Dostoevsky contrasts the arbitrariness of the underground man to a deterministic, scientistic vision of the world and makes it an important premise of his understanding of an authentic existence based on freedom and faith.